Belajar Toleransi Beragama di Lereng Menoreh Kabupaten Magelang - Nafilah Abdullah (UIN Sunan Kalijaga Yogyakarta, 2012)
This study aims to determine the slope of religious understanding Menoreh of religious about plurality and tolerance, and to know the attitude of religious tolerance in the slope Menoreh with people of other religions as well as to determine how the shape of religious Menoreh Magelang slope area facing intolerance that would undermine efforts religious tolerance are deeply embedded in the region?